Loving Under Power: Politics and Tradition Shaping Gay Love in Red, White & Royal Blue - Nabila Myisha; Linusia Marsih (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2026)
Queer romance in contemporary popular fiction has moved from marginal tragedy to more affirmative stories, yet less attention has been given to how such romance is negotiated inside institutions that depend on public image, tradition, and inherited norms. This article examines Casey McQuiston's novel Red, White & Royal Blue (2019), focusing on the relationship between Alex Claremont-Diaz, the First Son of the United States, and Prince Henry of the British royal family. Using a descriptive qualitative method and an extrinsic literary approach grounded in Annamarie Jagose's queer theory and Foucault's conception of sexuality and power as discussed by Spargo, this article analyses scenes where intimacy is shaped by external constraints. The findings show that politics turns Alex's sexual orientation into a campaign risk, royal tradition disciplines Henry through silence and continuity, and family expectations operate as both pressure and support. These forces produce a three-way dilemma in which queer love must be negotiated through vulnerability, strategy, and public affirmation. The article concludes that McQuiston presents queer romance as a relationship lived within and against institutional power, making love both emotionally intimate and politically meaningful.